Total cross-section measurements - Giacomelli, Giorgio (Progress in nuclear physics ;, 1970)
Total Cross-Section Measurements discusses the cross-sectional dimensions of elementary hadron collisions. The main coverage of the book is the resonance and high energy area of the given collision. A section of the book explains in detail the characteristic of a resonance region. Another section is focused on the location of the high energy region of collision. Parts of the book define the meaning of resonance in nuclear physics. Also explained are the measurement of resonance and the identification of the area where the resonance originates. Different experimental methods to measure the tota.